Validation of the instrument to measure attitudes toward gender equality in university students in Peru - Jose Calizaya Lopez; Jorge Rolando Paredes Rondon; Barbara Eliana Coaguila Mitta; Roberto Cervantes Rivera; David Porras Garcia (Universidad Ciencia y Tecnología, 2024)
Good attitudes toward gender equality are a basic element that must be considered in the profile of university students, to train professionals with high academic, scientific, and technical skills, as well as high human quality and sensitivity to the environment. In this work, the instrument's psychometric properties related to attitudes towards gender equality were validated. The study was instrumental, involving 776 university students who were intentionally selected. Confirmatory factor analysis was performed, demonstrating that the original model presented a need for adjustments, being necessary to implement the model with the covariation between the errors, achieving that the adjustment indices are adequate (CFI=0.914 and TLI= 0.900) and good adjustments in the SRMR= 0.052 and RMSEA= 0.052, likewise, the reliability with Omega was 0.787. Achieving that the instrument achieves adequate indicators of validity and reliability.